THE MALAY SHAMAN AS ENTREPRENEUR: ETHNOGRAPHIC OBSERVATIONS - Stark, Alexander; Kurniawan, Yohan (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Non-Western business models have received a greater amount of attention in recent years. In this article, the researchers analyze the entrepreneurial concept of traditional Malay shamans. The researchers conducted qualitative research and focused on two shamans: one originates from a rural area and one resides in an urban environment. Furthermore, they lived in two geographical regions, namely Kelantan (Malaysia) and West Sumatra (Indonesia). The researchers closely studied the daily routines of the shamans and carried out unstructured interviews. It was detected that their entrepreneurial activities are embedded in a system of family relationships and that profit-making is of minor importance, particularly for the healer, who lives in a village with its own form of subsistence. Furthermore, the Malay shamans follow a flexible timetable and can be easily contacted by their patients and customers. They also use the terminology of the local worldview, which gives them the opportunity to become more popular.